Impact of COVID-19 Crisis on Rural Youth: Evidence from a Panel Survey and an Experiment - Bhaskar Chakravorty; Apurav Yash Bhatiya; Clément Imbert; Maximilian Lohnert; Poonam Panda; Roland Rathelot (Global Labor Organization (GLO), 2021)
This paper presents evidence on the short and long-term impact of the first COVID-19 wave on India's rural youth. We interviewed about 2,000 vocational trainees from Bihar and Jharkhand between March 2020 and March 2021. We report a stark difference between men and women: while many male workers took up informal employment, most female workers dropped out of the labour force. Using a randomised experiment, we find that a government supported digital job platform does not increase job search or employment. Our findings suggest that bridging the gap between rural youths and urban formal labour markets requires much more active and targeted policy interventions, especially for female workers.
Keywords: J2; J3; J6; J7; M5; 330; Youth unemployment; gender; vocational training; public policy